2015
DOI: 10.1002/mds.26208
|View full text |Cite
|
Sign up to set email alerts
|

Apathy in Parkinson's disease: A systematic review and meta‐analysis

Abstract: Apathy is a frequently reported neuropsychiatric symptom in Parkinson's disease (PD), but its prevalence and clinical correlates are debated. We aimed to address these issues by conducting a systematic review and meta-analysis. Embase, Medline/PubMed, and PsychINFO databases were searched for relevant studies. Data were extracted by two independent observers, using predefined extraction forms tailored specifically to the research question. From 1,702 titles and abstracts, 23 studies were selected. Meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
192
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(209 citation statements)
references
References 75 publications
13
192
4
Order By: Relevance
“…Several factors may account for these differences; in particular, our subjects showed a longer disease duration, older age, more advanced disease stage and greater motor impairment, and scored lower on cognitive tests. Most of these factors have been shown to be associated with the frequency of apathy in PD (den Brok et al, 2015). This insight is further supported by our finding of significant correlations between AES scores (both SE and CR) and those recorded on the UPDRS III and H-Y scales, and, at least in the SE version, also with the MMSE and FAB scores.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several factors may account for these differences; in particular, our subjects showed a longer disease duration, older age, more advanced disease stage and greater motor impairment, and scored lower on cognitive tests. Most of these factors have been shown to be associated with the frequency of apathy in PD (den Brok et al, 2015). This insight is further supported by our finding of significant correlations between AES scores (both SE and CR) and those recorded on the UPDRS III and H-Y scales, and, at least in the SE version, also with the MMSE and FAB scores.…”
Section: Discussionsupporting
confidence: 80%
“…In our sample, apathy was found to affect the majority of the patients, as shown both by selfratings and informant ratings. The percentage of apathetic subjects was higher than that reported in the literature (den Brok et al, 2015), and the AES-SE scores were higher than those reported in the study by Santangelo et al (2014) in de novo untreated Italian PD patients. Several factors may account for these differences; in particular, our subjects showed a longer disease duration, older age, more advanced disease stage and greater motor impairment, and scored lower on cognitive tests.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Apathy, a disorder of motivation characterized by reduced self‐initiated goal‐directed behavior,1 is very common in Parkinson's disease (PD) and associated with diminished quality of life 2, 3, 4. Theoretical accounts5 and new evidence6 suggest that rather than being a unitary construct, apathy is multidimensional, involving behavioral, cognitive, executive, social, and emotional domains.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of apathy in PD varies from 17-70%, depending on the assessment procedures and the characteristics of the population [2,[5][6][7][8]. A recently published systematic review, and meta-analysis found that apathy affects about 40% of patients with PD [9] Several studies have indicated that apathy is correlated with cognitive impairments in patients with PD [4,7,[10][11][12][13][14][15][16][17][18]. For instance, a study investigated cognitive abilities in a patient group (23 with apathy and 25 without apathy) using the Apathy Evaluation Scale (AES) [19] and digit span [20], the Delis-Kaplan Executive Function Test [21], the California Verbal Learning Test [22] and the Wisconsin Card Sorting Test (WCST) [23].…”
Section: Introductionmentioning
confidence: 99%